Concepções de natureza e território na visão dos professores Guarani da escola indígena de Dourados/MS - Lima, Salvadora Caceres Alcântara (2012)
The thesis is about the Guarani people who lives in the city of Dourados, Mato Grosso do Sul region of Brazil's border with Paraguay. The indigenous population living in this municipality is quite significant. There are about 13,000 people from ethnicities Guarani Ñandeva Guarani Kaiowá, and Terena who share the same geographical area divided between two villages Jaguapiru and Bororó. The present study emphasizes the conceptions of the world Guarani teachers in relation to the nature and to the territory, based on the hypothesis that there is knowledge and knowledge of the people themselves and that are being shared throughout the generations through speaking and educational practices that can dispense with the school space. As research strategy was used the methodology of participant research for being the closest of my intention which was to conceive the teacher and the teacher Guarani as subjects of the research partners. From the reports collected about the trajectories of lives, locations of the villages where they were born and the school experiences they had, it was possible to retrieve a historical memory that portray a way to relate to nature and the territory and its importance for the update of the experiences and the affective links with spaces where they live or lived the ancestors Guarani.The fieldwork and interviews with teachers Guarani indigenous schools of Gold made it possible to discuss some aspects of the design of nature and people's own territory Guarani articulated knowledge organized scientifically by Western society. I understand how this knowledge can contribute to the construction of an educated and differentiated education that most closely matches the Guarani way of life. The analyses of the testimonials revealed that the spatial trajectory constitutes one of the central aspects in the organization of social life Guarani based primarily in language, economy of reciprocity and kinship relationship. These reflections far from a consensus plan to contribute to the debate for the construction of a critical view of society and the social function of the school and the curriculum within the villages of Dourados and beyond. In order to respect, value and incorporate the other knowledge and cultural and linguistic practices characteristic of coexistence in border areas.